Gender and socioeconomic level differences in resilience in adolescents - Prado-Álvarez, Rodolfo (2003)
We investigated if there were significant differences in resilience areas about gender and social status in adolescences from 12 to 14 years old, in three schools of Lima consideres typical to this 3 levels (high-medium-low). The design was comparative descriptive and was applied the Resilience Scale for Adolescences (ERA) which was built, validity and standardized by Prado and Del Águila (2000) bases on wollin and wollin theory. Respecting with the gender, we found that there wasn’t significant difference in the total Resilience punctuation, but there were significant differences in the Interaction Area in favor of the female about social status, we didn’t find significant difference in the total punctuation; eventhought there were significant differences in Interaction Area and Creativity Area in favor of the lowest status, and Iniciative Area in favor to the highest status.